Absorbable tissue adhesion material as well as preparation method and application thereof
By heating the lipoic acid monomer and polymerizing under ultraviolet light, lipoic acid polymers with excellent tissue adhesion, anti-inflammatory and antioxidant properties were prepared, which solved the storage stability and biodegradability of existing materials. The problem of difficulty in taking into account between the two achieves stable adhesion and gradual degradation of the materials in the body.
Patent Information
- Application Number
- CN202411626998.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
The long-term stability maintenance of existing tissue adhesion materials during storage and stable adhesion in humid physiological environments is difficult to coexist, and it is difficult to gradually degrade into biocompatible metabolites during tissue repair.
Lipoic acid polymers are prepared by heating the lipoic acid monomer powder and ultraviolet polymerization in the presence of or without polyphenols, which have excellent tissue adhesion, anti-inflammatory and anti-oxidation characteristic.
It achieves long-term storage stability of the material and biodegradability in the body, has excellent body fluid barrier performance, can quickly and effectively prevent postoperative body fluid leakage and reduce the risk of infection and postoperative complications.
Smart Images

Figure CN119505240A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical materials, and in particular to an absorbable tissue adhesion material and a preparation method and application thereof. Background Art
[0002] Tissue adhesion materials have attracted widespread attention in the biomedical field and show broad application prospects, including wound dressings, wearable devices and 3D printing. Common tissue adhesives on the market, such as Baxter's Coseal surgical auxiliary adhesive, are widely used in clinical surgery to reduce wound exposure and improve surgical outcomes. However, due to weak adhesive strength, these products are usually only used for auxiliary suturing.
[0003] To solve this problem, many studies have turned to enhancing the performance of adhesive materials, mainly by enhancing the overall dissipation capacity of adhesive materials and the interaction at the interface between tissue and materials (J. Li et al. Tough adhesives for diverse wet surfaces [J]. Science, 2024, 357, 378-381). Most of the current work focuses only on improving the interfacial bonding strength of tissue adhesive materials in wet environments, but the long-term storage stability of tissue adhesive materials during storage and the coexistence of stable adhesion in wet physiological environments have become a major challenge. At the same time, the ability to gradually degrade into biocompatible metabolites in enzymatic, oxygen-containing and aqueous environments during tissue repair is another requirement for tissue adhesion materials. However, in the process of tissue repair, how to maintain the long-term stability of tissue adhesion materials during storage and at the same time achieve the biodegradability of the materials is a key issue that needs to be solved urgently.
[0004] α-Lipoic acid (TA) is a coenzyme found in mitochondria and is involved in mitochondrial activity and synergistic energy metabolism. Currently, TA has been used to prepare supramolecular polymer adhesives based on its ring-opening self-polymerization (ROP) mechanism initiated by dynamic disulfide bond exchange and abundant adhesive carboxyl groups. TA is reported to undergo thermal, ionic and controlled radical ring-opening polymerization (Subhajit Pal et al. Recyclable surgical, consumer, and industrial adhesives of poly (α-lipoic acid) [J]. Science, 2024, 385, 877-883).
[0005] TA polymers can be used in various practical environments and are suitable for closed-loop recycling, but they spontaneously depolymerize under conditions relevant to many practical applications. Although polylipoic acid (PTA)-based supramolecular polymers can be stabilized by introducing multiple double-bonded monomers, metal ions, and ionic liquids into the system, the resulting PTA-based polymers are difficult to purify, and the prepared PTA processing methods are limited and cannot meet the needs of a variety of different tissue repair materials.
[0006] Therefore, developing a tissue adhesive material that can be applied to a variety of biological tissues, can be absorbed in the body and has good stability is still a technical gap that needs to be filled in the current market. Summary of the invention
[0007] In view of the above technical problems and the shortcomings in the art, the present invention provides an absorbable tissue adhesion material and a preparation method and application thereof. The absorbable tissue adhesion material of the present invention is a degradable polymer material with excellent tissue adhesion and anti-inflammatory and antioxidant properties.
[0008] [1] A method for preparing an absorbable tissue adhesion material, comprising:
[0009] The lipoic acid monomer powder is heated to perform a polymerization reaction, and the obtained polymer is subjected to ultraviolet light polymerization in a solution in the presence or absence of polyphenol to obtain a lipoic acid polymer, i.e., an absorbable tissue adhesion material;
[0010] The ultraviolet light intensity of the ultraviolet polymerization is 20 to 100 W / cm 2 , for example 50W / cm 2 The ultraviolet light band is 250-500nm, such as 254nm, 365nm, 400nm, etc. The ultraviolet light intensity and ultraviolet light band should be strictly within this range. If it exceeds the limited range, it may cause insufficient energy to destroy the disulfide bond in the five-membered ring or cause the polymer molecular chain to break.
[0011] In some embodiments, the preparation method of the present invention is a preparation method without metal involvement.
[0012] In some embodiments, the mixed solution formed after UV polymerization in the preparation method of the present invention can be used directly or further diluted with a solvent to prepare an absorbable tissue adhesion material in the form of a coating. The solvent may include at least one of ethanol, methanol, tetrahydrofuran, N,N-dimethylformamide, and dimethyl sulfoxide.
[0013] The lipoic acid monomer may include one or more of: R-α-lipoic acid (CAS: 1200-22-2), S-α-lipoic acid (CAS: 1077-27-6), DL-α-lipoic acid (CAS: 1077-28-7); or,
[0014] One or more of R-alpha lipoic acid, S-alpha lipoic acid, DL-alpha lipoic acid-NHS (CAS: 40846-94-4) and DL-alpha lipoic acid.
[0015] In some embodiments, the lipoic acid monomer may include one or more of R-α-lipoic acid, S-α-lipoic acid, DL-α-lipoic acid-NHS and DL-α-lipoic acid, and based on the mass of DL-α-lipoic acid being 100%, the mass fraction of one or more of R-α-lipoic acid, S-α-lipoic acid, DL-α-lipoic acid-NHS is 0.5%-10%.
[0016] The polyphenols may include one or more of tannic acid, epigallocatechin gallate, quercetin, kaempferol, catechin, anthocyanin, and caffeic acid.
[0017] The mass ratio of the polyphenol to the lipoic acid monomer may be 0 to 25:100, and further may be 0.001 to 25:100, for example, 0.01:100, 0.1:100, 0.174:100, 0.22:100, 1.74:100, 2.22:100, 4.12:100, 7:100, 22.2:100, and the like.
[0018] In the preparation method, the temperature for heating the lipoic acid monomer powder for polymerization reaction can be 70-120° C., such as 80° C., 100° C., etc., and the time can be 1-12 hours, such as 2 hours, etc.
[0019] In the preparation method, the ultraviolet polymerization time can be 300 to 1800 seconds, such as 600 seconds.
[0020] In the preparation method, the solvent in the solution may include at least one of ethanol, methanol, tetrahydrofuran, N,N-dimethylformamide, and dimethyl sulfoxide.
[0021] According to the preparation method, the concentration of the obtained polymer in the solution can be 10-400 mg / mL, such as 200 mg / mL.
[0022] [2] An absorbable tissue adhesion material prepared according to the preparation method described in [1].
[0023] In some embodiments, the absorbable tissue adhesion material is metal-free.
[0024] [3] Use of the absorbable tissue adhesion material according to [2] in the manufacture of a solid body material, a coating material or an injectable liquid material. Further, the thickness of the coating material may be 0.1 to 500 μm, such as 20 μm, 100 μm, etc.
[0025] When the absorbable tissue adhesion material is used to prepare a main solid material, the solvent can be removed based on the preparation method described in [1] to obtain a lipoic acid polymer solid.
[0026] When the absorbable tissue adhesion material is used as the main body material, a product of a specific shape can be obtained through conventional polymer processing methods such as molding, extrusion, injection molding, casting and 3D printing. The cross-linkable disulfide bonds of the lipoic acid monomer can be internally cross-linked by heating or ultraviolet light to ensure the chemical stability of the product.
[0027] In some embodiments, the absorbable tissue adhesion material can be used to make a coating material or an injectable liquid material. Furthermore, the absorbable tissue adhesion material can be evenly dispersed in a solvent to form an injectable liquid material, or further transferred to the surface of a substrate to form a coating material. For the needs of coating, different coating methods can be selected to apply a mixed solution containing the absorbable tissue adhesion material to the surface of the material, and the coating method includes but is not limited to ultrasonic atomization spraying, solution dipping, spin coating, etc. For the needs of injectable liquid materials, the solvent used to evenly disperse the absorbable tissue adhesion material can be dimethyl sulfoxide, etc., and the mass concentration of the absorbable tissue adhesion material evenly dispersed in the solvent can be 10% to 50%.
[0028] The mechanism of the tissue adhesion performance of the absorbable tissue adhesion material of the present invention is as follows: the hydrophobic polymer lipoic acid displaces water from the tissue surface under pressure, and its carboxyl group can form multiple hydrogen bonds and electrostatic interactions with the amino groups on the tissue surface to achieve rapid and firm adhesion to the tissue.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention innovates the preparation process of polylipoic acid: first, oligomers are formed by thermal polymerization, and then polyphenol compounds are introduced, and further cured under ultraviolet light, thereby realizing a linear polymer of covalent grafting of polyphenols and polylipoic acid polymers. This innovative two-step polymerization process ensures the linear characteristics of polylipoic acid molecules, and at the same time enables polyphenols to be efficiently grafted to the polymer ends. Compared with the existing metal-dependent synthesis methods, the method of the present invention not only does not require metal participation, but also can further significantly prolong the depolymerization time of the polymer, significantly improve the stability of the polymer and the long-term sustained release effect of lipoic acid monomers and polyphenols, and greatly prolong the material adhesion ability and anti-inflammatory and antioxidant effect time. In addition, the introduction of polyphenols also gives the polymer coating the dual characteristics of anti-inflammatory and antioxidant. By the method of first thermal polymerization and then ultraviolet light curing, the viscosity of the polylipoic acid solution after thermal polymerization can be significantly reduced, so that it can reach an ideal spraying viscosity, which is convenient for coating production. This unique preparation method enables the polylipoic acid material obtained by the present invention to have significant and long-lasting anticoagulant, anti-inflammatory and antioxidant properties while maintaining excellent and sustained tissue adhesion.
[0031] (2) The absorbable tissue adhesion polymer material obtained by the present invention has good processability. The main material can be obtained by molding, extrusion, injection molding, casting and 3D printing, and the drug balloon coating can also be prepared by processing methods such as dipping and spraying, and the injectable liquid adhesive can be prepared by solvent selection. Therefore, its applicability is far greater than most tissue adhesion materials on the market.
[0032] (3) The polylipoic acid tissue adhesive material prepared by the present invention not only has long-term storage stability, but also has stable tissue adhesion and biodegradability, and can effectively balance the storage stability of the material and the tissue absorption requirements in the application. Compared with commercially available tissue adhesive materials, the innovative preparation process of the present invention enables the tissue adhesive material to be gradually degraded in the body without toxic side effects, solving the problems of foreign body rejection and secondary wound damage caused by traditional sutures or metal fasteners. In addition, the material also has excellent body fluid barrier properties, which can quickly and effectively prevent postoperative body fluid leakage, thereby further reducing the risk of infection and postoperative complications. This innovation fills the gap in the current market for long-term stable, absorbable, and efficient tissue adhesive materials, and has extremely high clinical application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The following are photos of the coatings of Example 1 and Comparative Example 1 immediately and 60 days later.
[0034] Figure 2 The bursting pressure diagrams of the coating of Example 1 (PTAE) and the coating of Comparative Example 1 (PTA) immediately and after 3 days.
[0035] Figure 3 This is a graph showing the antioxidant properties of the polylipoic acid-polyphenol tissue adhesive material of Example 2.
[0036] Figure 4 This is a graph showing the adhesion performance of the polylipoic acid-polyphenol material in vascular tissues according to Example 3.
[0037] Figure 5 This is the 7-day release graph of lipoic acid monomers from the polylipoic acid-polyphenol material of Example 3. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0039] Example 1
[0040] PTAE-1% absorbable tissue adhesion material and its preparation
[0041] (1) Synthesis of lipoic acid polymer:
[0042] 5 g of DL-α lipoic acid monomer was heated at 80 °C for 2 h, and ethanol was used as a solvent to dissolve the oligomer to a final concentration of 200 mg / mL. 0.111 g of epigallocatechin gallate (EGCG) was added to dissolve in the oligomer solution. Subsequently, ultraviolet light was used to further polymerize the lipoic acid, and the irradiation intensity was 50 mW / cm 2 , irradiation time 10min, ultraviolet light wavelength 365nm, to obtain lipoic acid polymer (PTAE-1%) with EGCG as DL-α lipoic acid molar fraction of 1%.
[0043] (2) Preparation of absorbable tissue adhesion coating:
[0044] The PTAE-1% polymer solution obtained in step (1) was diluted to 10 mg / mL with ethanol as solvent, and a coating with a thickness of 100 μm was prepared by ultrasonic spraying technology.
[0045] Comparative Example 1
[0046] Preparation of PTA absorbable materials and coatings
[0047] (1) Synthesis of lipoic acid polymer:
[0048] 5 g of DL-α lipoic acid monomer was heated at 80° C. for 2 h, and ethanol was used as a solvent to dissolve the oligomer into a concentrated solution with a final concentration of 200 mg / mL to obtain lipoic acid polymer (PTA).
[0049] (2) Preparation of biological antifouling coating:
[0050] The concentrated polylipoic acid solution obtained in step (1) is used to prepare a coating with a thickness of 100 μm by using a dip coating technique.
[0051] Figure 1 The actual photos of the coatings of Example 1 and Comparative Example 1 immediately and after 60 days are shown. The coatings of Example 1 and Comparative Example 1 were placed at room temperature for 60 days ( Figure 1 ), the experimental results show that compared with the coating of Example 1 prepared by the method of the present invention, the coating material of Comparative Example 1 depolymerizes after 60 days to form a large amount of yellow opaque solid, which indicates that the ultraviolet polymerization and polyphenols of the present invention give the polylipoic acid coating the ability to be stored stably for a long time.
[0052] The coating materials of Example 1 and Comparative Example 1 were adhered to the inner surface of a bovine heart tube to test their bursting pressure immediately and after 3 days ( Figure 2 ). A hole with a diameter of 3.5 mm was made on the bovine heart tube. During the injection of deionized water (3 mL / min), the maximum pressure displayed on the digital pressure gauge screen was recorded as the bursting pressure. Compared with Comparative Example 1, Example 1 immediately exhibited excellent tissue adhesion performance, and the adhesion ability did not decrease significantly after 3 days. However, Comparative Example 1 depolymerized after 3 days, resulting in substantially no adhesion ability (<50 mmHg, lower than normal human blood pressure), which indicates that the polylipoic acid tissue adhesion material can maintain long-term stable wet tissue adhesion ability under the action of ultraviolet polymerization and polyphenols of the present invention.
[0053] Example 2
[0054] PTAE-10% absorbable tissue adhesion material and coating preparation
[0055] (1) Synthesis of lipoic acid polymer:
[0056] 5 g of DL-α-lipoic acid monomer was mixed with 1% DL-α-lipoic acid-NHS and heated at 80°C for 2 h. Ethanol was used as a solvent to dissolve the oligomer to a final concentration of 200 mg / mL. 1.11 g of epigallocatechin gallate (EGCG) was added to the oligomer solution and dissolved. Then, ultraviolet light was used to further polymerize the lipoic acid. The irradiation intensity was 50 mW / cm 2 , irradiation time 10min, UV band 254nm, to obtain lipoic acid polymer (PTAE-10%) with EGCG as DL-α lipoic acid molar fraction of 10%.
[0057] (2) Preparation of absorbable tissue adhesion coating:
[0058] The PTAE-10% polymer solution obtained in step (1) was diluted to 10 mg / mL with ethanol as solvent. A coating with a thickness of 20 μm was prepared by dip coating. The coating material of Example 2 was incubated in a constant temperature shaker at 37° C. for 24 hours, and the supernatant was taken to characterize its free radical scavenging ability using a hydrogen peroxide kit and a superoxide anion free radical scavenging kit. Figure 3 For the coating antioxidant capacity test, phosphate buffered saline (PBS) was used as the negative group. The results showed that Example 2 had a free radical scavenging capacity of more than 90%, laying a foundation for its anti-inflammatory and antioxidant capacity as a drug balloon coating in clinical practice.
[0059] Example 3
[0060] Preparation of PTAE-0.1% absorbable tissue adhesion bulk material
[0061] (1) Synthesis of lipoic acid polymer:
[0062] 5 g of R-α lipoic acid monomer was heated at 80°C for 2 h, ethanol was used as a solvent to dissolve the oligomer to a final concentration of 200 mg / mL, and 0.011 g of epigallocatechin gallate (EGCG) was added to dissolve in the oligomer solution. Subsequently, lipoic acid was further polymerized by ultraviolet radiation with an irradiation intensity of 50 mW / cm 2 , irradiation time 10min, UV band 254nm, to obtain lipoic acid polymer (PTAE-0.1%) with EGCG as R-α lipoic acid molar fraction of 0.1%.
[0063] (2) Preparation of absorbable tissue adhesion body:
[0064] Pour 1 mL of the PTAE-0.1% polymer solution obtained in step (1) into a polytetrafluoroethylene mold using ethanol as a solvent, and after the ethanol evaporates, obtain the PTAE-0.1% bulk material.
[0065] Figure 4 The immediate tissue adhesion ability of the main material of Example 3 was evaluated. The specific experimental steps are as follows: First, a circular notch with a diameter of 5 mm was cut in the center of the bovine heart tube tissue sample to simulate vascular damage. Then, trypan blue solution was used as a simulated blood flow medium. In the experiment, the main material of Example 3 was gently pressed to the incision for 5 seconds. The results showed that the material can quickly stop the simulated blood flow, proving its excellent adhesion to vascular tissue in a wet environment. The experimental results show that the developed coating material has the potential to quickly stop bleeding and seal vascular damage, which provides an experimental basis for the application of this material in the biomedical field, especially in the repair of vascular damage.
[0066] The degradability of the bulk material of Example 3 is represented by the release rate of R-α lipoic acid monomer ( Figure 5 ). First, the material was immersed in physiological saline and then placed in a 37°C constant temperature shaker. The absorbance of the supernatant at a wavelength of 333 nm was measured at different time points using a UV-visible spectrophotometer, and the concentration of the monomer in the supernatant was calculated using a standard curve. The results showed that the polylipoic acid material of Example 3 could slowly degrade and release anti-inflammatory lipoic acid monomer small molecules under a simulated physiological environment within seven days.
[0067] Example 4
[0068] PTAT-0.5% absorbable tissue adhesion material and coating preparation
[0069] (1) Synthesis of lipoic acid polymer:
[0070] 5 g of S-α lipoic acid monomer was heated at 100 °C for 2 h, ethanol was used as a solvent to dissolve the oligomer to a final concentration of 200 mg / mL, and 0.206 g of tannic acid was added to dissolve in the oligomer solution. Subsequently, ultraviolet light was used to further polymerize the lipoic acid, and the irradiation intensity was 50 mW / cm 2 , irradiation time 10min, ultraviolet light band 500nm, to obtain lipoic acid polymer (PTAT-0.5%) with tannic acid as S-α lipoic acid molar fraction of 0.5%.
[0071] (2) Preparation of absorbable tissue adhesion spray coating:
[0072] The PTAT-0.5% polymer solution obtained in step (1) was diluted to 20 mg / mL with ethanol as solvent and sprayed directly on the substrate using a commercial spray bottle to form a uniform coating.
[0073] Example 5
[0074] Preparation of PTAC-0.2% absorbable tissue adhesion coating material
[0075] (1) Synthesis of lipoic acid polymer:
[0076] 5 g of DL-α lipoic acid monomer was heated at 80 °C for 2 h, ethanol was used as a solvent to dissolve the oligomer to a final concentration of 200 mg / mL, and 0.0087 g of caffeic acid was added to dissolve in the oligomer solution. Subsequently, ultraviolet light was used to further polymerize the lipoic acid, and the irradiation intensity was 50 mW / cm 2 , irradiation time 10min, ultraviolet light wavelength 365nm, to obtain lipoic acid polymer (PTAC-0.2%) with caffeic acid as DL-α lipoic acid molar fraction of 0.2%.
[0077] (2) Preparation of absorbable tissue adhesion coating:
[0078] The PTAC-0.2% polymer solution obtained in step (1) was diluted to 10 mg / mL with ethanol as solvent, and a coating with a thickness of 20 μm was prepared by ultrasonic spraying technology.
[0079] Example 6
[0080] Preparation of PTAC-2% absorbable tissue adhesion bulk material
[0081] (1) Synthesis of lipoic acid polymer:
[0082] 5 g of DL-α lipoic acid monomer was heated at 80 °C for 2 h, ethanol was used as a solvent to dissolve the oligomer to a final concentration of 200 mg / mL, and 0.087 g of caffeic acid was added to dissolve in the oligomer solution. Subsequently, ultraviolet light was used to further polymerize the lipoic acid, and the irradiation intensity was 50 mW / cm 2 , irradiation time 10min, ultraviolet light wavelength 254nm, to obtain lipoic acid polymer (PTAC-2%) with caffeic acid as DL-α lipoic acid molar fraction 2%.
[0083] (2) Preparation of absorbable tissue adhesion bulk material:
[0084] Pour 1 mL of the PTAC-2% polymer solution obtained in step (1) into a polytetrafluoroethylene mold using ethanol as a solvent, and after the ethanol evaporates, obtain the PTAEC-2% bulk material.
[0085] Example 7
[0086] PTACT-5% absorbable tissue adhesion material and spray coating preparation
[0087] (1) Synthesis of lipoic acid polymer:
[0088] 5 g of DL-α lipoic acid monomer was heated at 80°C for 2 h, ethanol was used as a solvent to dissolve the oligomer to a final concentration of 200 mg / mL, and 0.35 g of catechin was added to dissolve in the oligomer solution. Subsequently, ultraviolet light was used to further polymerize the lipoic acid, and the irradiation light intensity was 50 mW / cm 2 , irradiation time 10min, ultraviolet light wavelength 400nm, to obtain lipoic acid polymer (PTACT-5%) with catechin as DL-α lipoic acid molar fraction of 5%.
[0089] (2) Preparation of absorbable tissue adhesion spray coating:
[0090] The PTACT-5% polymer solution obtained in step (1) was diluted to 50 mg / mL with ethanol as solvent and sprayed evenly on the substrate using a commercial spray bottle to prepare a uniform coating.
[0091] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing an absorbable tissue adhesion material, characterized in that: include: The lipoic acid monomer powder is heated to perform a polymerization reaction, and the obtained polymer is subjected to ultraviolet light polymerization in a solution in the presence or absence of polyphenol to obtain a lipoic acid polymer, i.e., an absorbable tissue adhesion material; The ultraviolet light intensity of the ultraviolet polymerization is 20 to 100 W / cm 2 , the ultraviolet light band is 250~500nm.
2. The preparation method according to claim 1, characterized in that: The lipoic acid monomer comprises: One or more of R-α-lipoic acid, S-α-lipoic acid, DL-α-lipoic acid; or, One or more of R-alpha lipoic acid, S-alpha lipoic acid, DL-alpha lipoic acid-NHS and DL-alpha lipoic acid.
3. The preparation method according to claim 1, characterized in that: The lipoic acid monomer includes one or more of R-α-lipoic acid, S-α-lipoic acid, DL-α-lipoic acid-NHS and DL-α-lipoic acid, and based on the mass of DL-α-lipoic acid being 100%, the mass fraction of one or more of R-α-lipoic acid, S-α-lipoic acid, DL-α-lipoic acid-NHS is 0.5%-10%.
4. The preparation method according to claim 1, characterized in that: The temperature of heating the lipoic acid monomer powder for polymerization reaction is 70 to 120° C. and the time is 1 to 12 hours; The ultraviolet polymerization time is 300 to 1800 seconds.
5. The preparation method according to claim 1, characterized in that: The solvent in the solution includes at least one of ethanol, methanol, tetrahydrofuran, N,N-dimethylformamide, and dimethyl sulfoxide; The concentration of the obtained polymer in the solution is 10 to 400 mg / mL.
6. The preparation method according to claim 1, characterized in that: The polyphenols include one or more of tannic acid, epigallocatechin gallate, quercetin, kaempferol, catechin, anthocyanin, and caffeic acid; The mass ratio of the polyphenol to the lipoic acid monomer is 0 to 25:100, and further 0.001 to 25:
100.
7. The absorbable tissue adhesion material prepared according to the preparation method according to any one of claims 1 to 6.
8. The absorbable tissue adhesion material according to claim 7, characterized in that: The absorbable tissue adhesion material is metal-free.
9. Use of the absorbable tissue adhesion material according to claim 7 or 8 in making a main solid material, a coating material or an injectable liquid material.
10. The use according to claim 9, characterized in that: The absorbable tissue adhesion material is used to prepare a coating material or an injectable liquid material; the absorbable tissue adhesion material is uniformly dispersed in a solvent to form an injectable liquid material, or further transferred to the surface of a substrate to form a coating material.
Citation Information
Patent Citations
Anti-tumor nano-drug
CN108553458A
Preparation method of photo-crosslinking dynamic reversible supramolecular polymer adhesive based on lipoic acid small molecular compound
CN113061263A
Solvent-free binder, and preparation method and application thereof
CN113621342A
Activatable high-adhesion polymer material as well as preparation method and application thereof
CN116082638A
Adhesive as well as preparation method and application thereof
CN118787773A
Cited By
Breathable data glove and preparation method thereof
CN119924601A